6(2z-3)-4=3(5z-7)

Simple and best practice solution for 6(2z-3)-4=3(5z-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2z-3)-4=3(5z-7) equation:


Simplifying
6(2z + -3) + -4 = 3(5z + -7)

Reorder the terms:
6(-3 + 2z) + -4 = 3(5z + -7)
(-3 * 6 + 2z * 6) + -4 = 3(5z + -7)
(-18 + 12z) + -4 = 3(5z + -7)

Reorder the terms:
-18 + -4 + 12z = 3(5z + -7)

Combine like terms: -18 + -4 = -22
-22 + 12z = 3(5z + -7)

Reorder the terms:
-22 + 12z = 3(-7 + 5z)
-22 + 12z = (-7 * 3 + 5z * 3)
-22 + 12z = (-21 + 15z)

Solving
-22 + 12z = -21 + 15z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-15z' to each side of the equation.
-22 + 12z + -15z = -21 + 15z + -15z

Combine like terms: 12z + -15z = -3z
-22 + -3z = -21 + 15z + -15z

Combine like terms: 15z + -15z = 0
-22 + -3z = -21 + 0
-22 + -3z = -21

Add '22' to each side of the equation.
-22 + 22 + -3z = -21 + 22

Combine like terms: -22 + 22 = 0
0 + -3z = -21 + 22
-3z = -21 + 22

Combine like terms: -21 + 22 = 1
-3z = 1

Divide each side by '-3'.
z = -0.3333333333

Simplifying
z = -0.3333333333

See similar equations:

| y+3(15-25)+25=40 | | -56x^3y^4-32x^6y^3= | | m/16=0.5 | | (4x^2-9)/(2x^2-3x) | | 3p-q=3.6 | | x+(x+12)=90 | | 4x^2-16x-y^2-2y+8z^2+8z+17=0 | | 26x^2-23xy+5y^2= | | 336-8x=13x | | 2p=-q+49 | | -1(x-6)=8x-72 | | j/12=11 | | y+2(5-25)+20=30 | | 2x^2-0=64 | | h/13=13 | | 4x^2-16x-y^2-2+8z^2+8z+17=0 | | 6x+3=2x-7-2x | | 40x^2-140=500 | | V=s^3 | | x^2+15xy+54y^2= | | 6n^2+30n-9=0 | | 2y-3-678=500 | | 6x+15x^2+6x^3=0 | | 3x+13=6y | | u^2-12u-15=0 | | 6/t^3=0 | | 6/t^3 | | 6x+-2+8=x+5 | | s^3+4*s^2+10*s+40=0 | | 4sin(3x)=2 | | X-4=-3.4 | | v/5=85 |

Equations solver categories